Identification of Factors Influencing the Design of a Structural Model for Employees’ Unconventional Administrative Behaviors in Governmental Organizations Using Grounded Theory - Chashm Barah , Elham; Mahbibi, Seraj al-Din; Ameri Shahrabi , Mohsen (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The purpose of this study was to identify the factors influencing the design of a structural model for employees’ unconventional administrative behaviors in governmental organizations using grounded theory. Methodology: The research methodology employed both qualitative and quantitative approaches. Data were collected through interviews. The study population included experts, academics, and specialists in the research field, with no fixed limit, and 18 individuals were selected until theoretical saturation was reached. The sampling method was snowball sampling. Primary data were collected via interviews. In line with methodological procedures, during the three stages of open coding, axial coding, and selective coding, relevant codes were extracted from a large volume of primary data. Subsequently, through the constant comparison method, a concept was extracted from several codes, and similarly, other codes were transformed into concepts, yielding a total of 93 concepts. In the next stage, several concepts were categorized into one theme, resulting in 20 themes for this study. Findings: The study findings indicated that two themes emerged as central categories: legal and regulatory weaknesses and weaknesses in human resource management systems. Other themes were categorized into five groups for presentation in the model: causal conditions (4 themes), context (4 themes), intervening conditions (3 themes), strategies (3 themes), and outcomes (4 themes). Conclusion: Managers in governmental organizations should make every effort to leverage effective human resources, policies, and programs, and develop content strategies with a particular focus on employees’ unconventional administrative behaviors within organizational processes to achieve more effective outcomes.